2005
DOI: 10.1080/10556790500497311
|View full text |Cite
|
Sign up to set email alerts
|

Be–X-ray binaries and candidates

Abstract: We present a compilative catalogue of Be/X-ray binaries and candidates in the Galaxy and in the Large and Small Magellanic Clouds. This catalogue contains 130 sources and provides information on names and spectral types of optical components, distances, spin characteristics of neutron stars, and on orbital and X-ray properties of binary systems. We give brief comments on each object and provide necessary references to original data.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
97
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(99 citation statements)
references
References 182 publications
(307 reference statements)
1
97
1
Order By: Relevance
“…Throughout explicitly excluding the brightening of the source caused by circumstellar emission leads to a underestimation of the distance. In two cases, our distance determinations are much higher than those quoted in Raguzova & Popov (2005). In both 7.9 ± 1.2/5.9 ± 0.9 3.8 RP05 GROJ1008-57 9.7 ± 0.8/5.8 ± 0.5 2.0 RP05 XTE 1946+27…”
Section: Milky Way Starscontrasting
confidence: 65%
See 1 more Smart Citation
“…Throughout explicitly excluding the brightening of the source caused by circumstellar emission leads to a underestimation of the distance. In two cases, our distance determinations are much higher than those quoted in Raguzova & Popov (2005). In both 7.9 ± 1.2/5.9 ± 0.9 3.8 RP05 GROJ1008-57 9.7 ± 0.8/5.8 ± 0.5 2.0 RP05 XTE 1946+27…”
Section: Milky Way Starscontrasting
confidence: 65%
“…NO01 cases, though, the discrepancy comes from the assumed parameters and has nothing to do with the method presented here. For example GRO J1008−57: the distance quoted in Raguzova & Popov (2005) was taken from a work by Haberl & Sasaki (2005). These last authors used, in turn, results from Macomb et al (1994).…”
Section: Milky Way Starsmentioning
confidence: 99%
“…Although there is a perceived deficiency of short-period Be star binaries (e.g., Abt & Levy 1978), recent work has led to the discovery of 55 Be star binaries with periods <100 days (Gies 2000;Raguzova & Popov 2005), and Be stars have been observed in nearly all stages of the proposed binary evolution scenario. The initially more massive star expands to fill its critical Roche lobe during the H shellburning phase, triggering Case B mass transfer and causing the spin-up of the mass gainer (Gies 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al (2004a) extended the application of the viscous decretion disc model of Okazaki and Negueruela (2001) to compact companions of arbitrary mass and showed that the most effective Be disc truncation would occur in relatively narrow systems. Using the population synthesis results of Podsiadlowski et al (2003), which state that binary black holes are most likely to be born in systems with narrow orbits (P orb 30 days), the reason for the lack of these systems can be attributed to the difficulty Liu et al (2007) and Liu et al (2006) catalogs plus update from the 4th IBIS/ISGRI soft gamma-ray survey catalog b Sources in the updated on-line version of the Raguzova and Popov (2005) catalog (http://xray.sai.msu.ru/ ∼ raguzova/BeXcat/) c Systems with known optical counterpart and verified X-ray behavior (from Table 1) to detecting them. Be/BH binaries are expected to be X-ray transients with very long quiescent states.…”
Section: High-mass X-ray Binariesmentioning
confidence: 99%